Toward high-quality education in Peru : standards, accountability, and capacity building. (World Bank country study., 2007)
This book has three main recommendations. First, it is necessary to generate basic standards, quality goals, and quality measurement systems. Second, once quality can be measured, a clear system of accountability should be implemented based on these standards and quality goals. The clients will play a central role in these systems by demanding their rights to quality services; this will only become possible once there are standards and goals that clarify clients' rights. Third, once there are standards and systems of accountability, investment is needed to strengthen the institutional capacity.